Venous dysfunction plays a critical role in "normal" white matter disease of aging. (January 2021) - Kapadia, Anish; Dmytriw, Adam A.
Abstract: A ubiquitous finding on MRI in older individuals, age-related cerebral white matter hyperintensities (WMHs) are associated with cognitive decline, dementia, disability, and death. Currently, these findings are thought to represent small infarcts secondary to lipohyalinotic arteriosclerosis. Commonly though, the anatomic distribution of WMHs is often non-arterial, and parallel the deep venous system. Furthermore, there is discrepant evidence for the role of conventional vascular risk factors such as hypertension, carotid atherosclerosis and diabetes for the development and progression of these. Interventions targeting conventional vascular risk factors lack consistency in preventing the progression of WMHs. There is evidence for age-related hemodynamic cervical venous dysfunction resulting in reduced internal jugular vein venous compliance, venous dilatation, and venous reflux. Similarly, venous collagenosis increases with age. Increased blood–brain barrier (BBB) permeability is also noted with aging. Both hemodynamic venous dysfunction, venous sclerosis, and increased BBB permeability are associated with WMHs. We propose that age-related WMHs are a sequalae of venous dysfunction. Venous dysfunction results initially in increased transmission of venous pressures to the brain. Subsequent BBB disruption leads to increased permeability with progression to end-stage findings of age-related WMHs.